Let's Talk About Stereochemistry for a Moment: a Home Experiment Conducted with College Students in Social Isolation - Pamella Moreira Monte; Jose C. Barros; Tiago Lima da Silva (Orbital: The Electronic Journal of Chemistry, 2022)
Due to COVID-19, we are adjusting to a new educational environment while also being socially isolated. By combining previously established ways of remote education with video conferences, the world is creating a new sector termed techno-pedagogy. The concept of stereochemistry in Organic Chemistry is frequently difficult to understand even in classroom teaching. Plane-polarized light rotation is difficult to describe because it needs a high level of abstraction in the mental exercise. As a result, we propose in this work that technology be developed to teach stereochemistry remotely. As a result, we prepared a training video that shows college students how to execute a hand-made stereochemistry experiment. Lecturers, undergraduates, and graduate students all gave the video great scores.